2021
DOI: 10.1177/08862605211001471
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Dating Violence: Results of a Mixed Study in Quito, Ecuador

Abstract: Dating violence is a public health problem affecting people worldwide. This study evaluated the occurrence of different types of adolescent dating violence using a mixed analysis of each data source. The present study addresses the following research questions: does the occurrence of the types of violence analyzed in the quantitative phase match with the narratives obtained in the qualitative phase? and does the additional information obtained in the qualitative phase improve the understanding of the analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
2
8
0
1
Order By: Relevance
“…Female victims could have assumed this belief as their own, especially in traditional cultures such as Latin societies. This conclusion has been already pointed out by authors such as [ 38 ], who indicated that adolescents tend to assume the traditional gender role model. In this regard, Fernández et al [ 64 ] pointed out that, although girls in general showed a lower degree of acceptance of abusive behaviour and a higher level of perception of severity, as the frequency of abuse increased, the victimized girls also began to show greater acceptance of violence perpetrated by their partners and more sexist attitudes, which leads to a progressive normalization of violent behaviour.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Female victims could have assumed this belief as their own, especially in traditional cultures such as Latin societies. This conclusion has been already pointed out by authors such as [ 38 ], who indicated that adolescents tend to assume the traditional gender role model. In this regard, Fernández et al [ 64 ] pointed out that, although girls in general showed a lower degree of acceptance of abusive behaviour and a higher level of perception of severity, as the frequency of abuse increased, the victimized girls also began to show greater acceptance of violence perpetrated by their partners and more sexist attitudes, which leads to a progressive normalization of violent behaviour.…”
Section: Discussionsupporting
confidence: 60%
“…As a result, the more recognizable forms of gender stereotypes related with hostile sexism could have less importance in countries such as Spain. In contrast, the perpetuation of the assumption of traditional gender roles, which seems to be accepted by society in general, and adolescents in particular in Ecuador [ 38 ], may be the key to the maintenance of both gender gap and traditional gender stereotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este estudio está sujeto a limitaciones en cuanto a su generalización a tener presentes. Primera, la disimulación, esto es, la ocultación de características negativas o acciones antisociales o delictivas que se ha de sospechar en este contexto de evaluación, especialmente entre los varones (Bravo et al, 2018;Gracia-Leiva et al, 2019;Cárdenas et al, 2021Medina-Maldonado et al, 2021; y la tendencia a la responsabilización del otro miembro de la pareja de los conflictos (Fariña et al, 2020). Segunda, los sesgos en las respuestas del participante, la medida de la táctica de razonamiento/ argumentación está sujeta a un error muy grande (α combinado = .311), tal que no capta la gran mayoría de ésta.…”
Section: Discussionunclassified
“…In relation to physical violence, it continues to stand out and is the one subcomponent is most widely studied among the dating relationships of university students according to research conducted by a university in Spain and another in South Korea led by Arenas-Carbellido et al [26]. Similarly, in the study of Medina-Maldonado et al [27]; the most common violent relationships among adolescents are psychological, mild, and severe.…”
Section: Discussionmentioning
confidence: 99%